Accelerated alveolar bone loss in a mouse model of inflammatory bowel disease and its relationship with intestinal inflammation. Issue 10 (21st February 2022) - Qiao, Dan; Chen, Rixin; Li, Lingjun; Zhu, Feng; Zhang, Yangheng; Yan, Fuhua
Abstract: Background: Bone loss is a common complication of inflammatory bowel disease (IBD); however, few studies have focused on alveolar bone loss (ABL) in IBD. Herein, we systematically observed ABL in an interleukin (IL)‐10 knockout (IL‐10 –/– ) mouse model of IBD and explored the possible mechanisms. Methods: IL‐10 –/– and age‐matched wild‐type (WT) male mice were sacrificed every 2 weeks from 12 to 24 weeks of age. ABL was determined by microcomputed tomography. Periodontal and intestinal inflammation were evaluated using histological grading and inflammatory factor expression levels. Intestinal barrier integrity and cytokine levels in serum were examined by immunofluorescence and enzyme‐linked immunosorbent assays, respectively. The expression of macrophage phenotype markers, including inducible nitric oxide synthase (iNOS), arginase‐1 (Arg‐1), and bone metabolic markers, including osteoprotegerin, receptor activator of nuclear factor‐κB ligand (RANKL), were measured by immunohistochemistry. The macrophage phenotype in the periodontium was also examined by real‐time quantitative polymerase chain reaction. Results: Compared with WT mice, IL‐10 –/– mice exhibited significant ABL from 18 weeks of age. However, no significant differences were observed in the periodontium between the two groups in either histopathological scores or inflammatory factor levels. In the colon and ileum, these measurements significantly increased in IL‐10 –/– mice from 12 and 14 weeks, respectively. Correlation analysis also revealed that ABL in IL‐10 –/– mice was positively correlated with intestinal inflammation. Furthermore, IL‐10 –/– mice showed a destroyed intestinal barrier and higher serum levels of inflammatory factors. In both the intestine and periodontium, higher iNOS and lower Arg‐1 levels, along with an increase in RANKL expression in the periodontium, were examined in IL‐10 –/– mice. Conclusions: An accelerated ABL spontaneously occurred in IL‐10 –/– mice and was correlated more with inflammation of the intestine than periodontium. Immunopathological changes may be the potential cause of abnormal alveolar bone metabolism.